INTERACTION OF BIOSILICA BASED BIOMATERIAL FROM TROPICAL MARINE DIATOM WITH HUMAN BLOOD PROTEINS - Joan Manuela, Ilona
Recent research shows that biosilica from diatomaceous microalgae can be used as biomaterials, for example, biomaterials that make up bone implants, dental implants, drug delivery systems, and many more. However, in the body, the interaction of blood and biomaterials can trigger a series of complex events such as adsorption or coagulation of proteins, as well as adhesion or platelet aggregation. Therefore, this research aims to study the interaction profile between biosilica from diatoms and human blood proteins to develop biosilica as a compatible biomaterial. In this study, cultivation of Navicula salinicola NLA diatoms isolated from the Thousand Islands of Indonesia was carried out, followed by the process of extraction until pure biosilica was obtained as evidenced by FTIR spectrum analysis. The cultivation results showed that the initial cell density of Navicula salinicola NLA was 700,000 cells/mL which increased to 5,390,000 cells/mL after 12 days of growing in modified seawater media. The obtained biomass has a productivity of 5.34 g/L of culture. From the biomass, biosilica was successfully extracted with a productivity of 49.41 mg/L of culture. Biosilica is then mixed with human serum albumin (HSA) or human blood plasma to investigate the protein adsorption process. The results showed that the occurrence of protein adsorption follows pseudo-first-order kinetics. Thermodynamically, the adsorption of blood proteins by biosilica follows the Freundlich, Sips, and Temkin adsorption isotherm model. In addition, two different diatom species were also compared, namely Navicula salinicola NLA (pennate form diatom) and Cyclotella striata TBI (centrate form diatom). Based on the value of adsorption capacity at equilibrium (qe) and percentage of adsorbed protein, HSA is more effectively adsorbed by N. salinicola diatoms. At low protein concentrations, N. salinicola can absorb up to ±99% protein (qe = 101.26 mg/g), and C. striata up to ±40% protein (qe = 42.21 mg/g). At high protein concentrations, N. salinicola can absorb up to ±62% (qe = 379.15 mg/g), and C. striata up to ±56% (qe = 311.14 mg/g). Similar to albumin adsorption, human blood plasma is also more effectively adsorbed by N. salinicola diatoms (qe = 840.51 mg/g) compared to C. striata (qe = 770.77 mg/g).